2012
DOI: 10.1136/bjsports-2012-091011
|View full text |Cite
|
Sign up to set email alerts
|

Competition injuries in taekwondo: a literature review and suggestions for prevention and surveillance

Abstract: Rule changes should be considered and it is recommended that governing bodies employ qualified medical personnel. Establishing an ongoing injury surveillance system in taekwondo should be the first priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 31 publications
(54 reference statements)
3
70
1
6
Order By: Relevance
“…26 Although less frequent in overall number, upper extremity injuries in taekwondo may be more severe compared with lower extremity injuries. 27 The incidence of concussion in adult taekwondo ranges from 4.6 to 50.2 per 1000 athletic exposures, potentially up to 4 times higher than that in American football. 27,28 One study of adult Olympic taekwondo kicks, measured by a simulated head target, reported that the most common kick impacts used in taekwondo had acceleration and recorded impacts equivalent to or greater than documented concussive injuries in American football.…”
Section: Injury Riskmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Although less frequent in overall number, upper extremity injuries in taekwondo may be more severe compared with lower extremity injuries. 27 The incidence of concussion in adult taekwondo ranges from 4.6 to 50.2 per 1000 athletic exposures, potentially up to 4 times higher than that in American football. 27,28 One study of adult Olympic taekwondo kicks, measured by a simulated head target, reported that the most common kick impacts used in taekwondo had acceleration and recorded impacts equivalent to or greater than documented concussive injuries in American football.…”
Section: Injury Riskmentioning
confidence: 99%
“…27 The incidence of concussion in adult taekwondo ranges from 4.6 to 50.2 per 1000 athletic exposures, potentially up to 4 times higher than that in American football. 27,28 One study of adult Olympic taekwondo kicks, measured by a simulated head target, reported that the most common kick impacts used in taekwondo had acceleration and recorded impacts equivalent to or greater than documented concussive injuries in American football. 28 Taekwondo rule changes have awarded more points for kicks aimed at the head, which may increase the risk of concussion.…”
Section: Injury Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…The health benefits associated with regular participation in sports are well known, however; there is inherent risk associated with participation, and a number of studies have documented the incidence and prevalence of injuries across a wide range of sports [1][2][3][4][5] . Epidemiological evidence indicates that sports injuries are a major contributor to injuries in general and are associated with significant cost implications 6) .…”
Section: Introductionmentioning
confidence: 99%